Experiencing Etruscan pots : ceramics, bodies and images in Etruria - Shipley, Lucy (Archaeopress archaeology., 2015)
In a world without plastics, ceramics, alongside organic containers, were used for almost every substance which required protection or containment: from perfume to porridge. The experience of an Etruscan person, living day to day, would have been filled with interactions with ceramics, making them objects which can recall intimate transactions in the past to the archaeologist in the present. Characterising that experience of Etruscan pottery is the concern of this book. What was it like to use and live with Etruscan pottery? How was the interaction between an Etruscan pot structured and constituted? How can that experience be related back to bigger questions about the organisation of Etruscan society, its increasingly urban nature and relationship with other Mediterranean cultures?